Educative games and expositive lesson: Comparison of educational techniques on sitting posture - De Vitta, Alberto; De Vitta, Fabiana Cristina Frigieri [UNESP]; Gatti, Márcia Aparecida Nuevo; Simeão, Sandra Fiorelli de Almeida Penteado (My University, 2012)
Introduction: Studies on education in health are important for the concretion of action of promotion of the health. Objective: To verify the changes of theoretical knowledge on sitting posture, evaluated at two moments (initial and final,) considering two programs of education (expositive lesson and operative groups). Methods: 75 pupils had been citizens, of both the sexes, three 4as series of a public school, evaluated previously (A1) on seated position; group 1 was submitted to a procedure of expositive education, the 2 educative games in the 2 and, the 3 to no intervention. After one week they had been reevaluated (A2). For the moments the test of Wilcoxon was applied and between the Kruskal groups Wallis. Results: In the comparison inside of the groups, of 2 and 3 they had presented increase in the number of rightness on position seated in the after-test, with statistical significant difference, whereas in the group has controlled, such fact did not occur. In the comparison between groups, at the first moment (A1), 2 groups e 3 had not presented significant difference statistical (p > 0,05), however, in as moment notices that it had difference statistics between the three groups (p < 0,01), being that the G3 presented minor frequency of errors (md = 5) in relation to the g2 (md = 8) and g1 (md = 10). Conclusions: It can be affirmed that educative techniques that supply information and promote debates and exchanges of experiences between the participants increase the possibilities of incorporation of the contents related to the sitting posture.
Keywords: Education; Health; Sitting posture; Students; Teaching procedures